The Italian Water Industry Cases of Excellence (Springer International Publishing, 2018)
This book describes the water sector as it is structured in Italy, presenting innovative engineering, financial and managerial solutions implemented by the Italian water sector, through the experiences of its major stakeholders. The main themes addressed include water regulation, financing infrastructures, economic performance of the leading companies, abstraction, potabilization, distribution, treatment and purification technologies, energy production, and organizational restructuring. The last part of the work presents company profiles with important financial indicators, as well as future strategic postures. Written by leading Italian experts, the book reflects the remarkable advances that have been made in the field of water governance and environmental management. The book is especially valuable for researchers, water professionals, utility managers, as well as policy makers and foreign investors looking for opportunities. This work has been prepared as part of the research activities of the Observatory on Sustainable Water Industry, one of Agici's Research and Advisory units.